2014
DOI: 10.1007/s12032-014-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of osteopontin in osteosarcoma

Abstract: The primary bone malignancy osteosarcoma (OS) is a painful health burden, of which treatment remains a challenging problem. Identification of specific tumor biomarkers may help to investigate and develop the novel effective therapeutic approaches that have specific molecular target for the treatment of patients with OS. Osteopontin (OPN), a phosphorylated glycoprotein, is involved in many biological processes, such as biomineralization, bone remodeling and immune responses and has recently been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…OPN (Osteopontin), also known as SPP1, is a member of the small integrin-binding ligand N-linked glycoprotein (SIBLING) family and is secreted in mammalian cells. Secreted OPN has been discovered in tissue matrix, including bone, fibroblast, osteocyte, dendritic cells, macrophages, and activated T cells [ 22 ]. This study found immunohistochemical expression of OPN protein to be weakly positive in the stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…OPN (Osteopontin), also known as SPP1, is a member of the small integrin-binding ligand N-linked glycoprotein (SIBLING) family and is secreted in mammalian cells. Secreted OPN has been discovered in tissue matrix, including bone, fibroblast, osteocyte, dendritic cells, macrophages, and activated T cells [ 22 ]. This study found immunohistochemical expression of OPN protein to be weakly positive in the stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is widely held that the earlier these defects occur in the osteoblastic lineage, the more undifferentiated or aggressive the cancer cells [15,19-2 0] . Accordingly, more invasive OS cells are noted to have minimal expression of osteocalcin (OCN) and osteopontin (OPN), both of which are observed at higher levels in mature osteoblasts [21][22][23] . Another notable difference between late osteoprogenitors and OS tumor cells is the ability of the latter to evade senescence through an alternative lengthening of telomere (ALT) pathway [24] .…”
Section: Molecular Basis Of Os and Potential Targets For Therapymentioning
confidence: 99%
“…Furthermore, it is widely held that the earlier these defects occur in the osteoblastic lineage, the more undifferentiated or aggressive the cancer cells [ 15 , 19 - 20 ] . Accordingly, more invasive OS cells are noted to have minimal expression of osteocalcin (OCN) and osteopontin (OPN), both of which are observed at higher levels in mature osteoblasts [ 21 - 23 ] . Another notable difference between late osteoprogenitors and OS tumor cells is the ability of the latter to evade senescence through an alternative lengthening of telomere (ALT) pathway [ 24 ] .…”
Section: Molecular Basis Of Os and Potential Targets For Therapymentioning
confidence: 99%